Efficiency analysis of productive waqf management at Jogokariyan Mosque Yogyakarta - Jamagis, Alwaqiatul; Pakkanna, Mukhaer; Umam, Saiful (Indonesian Journal of Multidisciplinary Science, 2024)
Waqf plays an important role in promoting the welfare of society, especially in overcoming poverty and social inequality in Indonesia, a Muslim-majority country. This study aims to analyze the production efficiency of productive waqf management by Nazir in Jogokariyan Mosque Yogyakarta and identify problems in the management. The research method uses a quantitative approach with Data Envelopment Analysis (DEA) and Banxia Frontier Analyst software. Primary data comes from the Jogokariyan Mosque's finances managed by Nazhir waqf. The results showed that DMU 1 (lodging) achieved 100% efficiency in 2017, 2018, and 2019. DMU 2 (rice fields) achieved 100% efficiency from 2017 to 2023. Efforts to improve the efficiency of DMU 1 involve successively reducing the input variables of employee salaries (10.42%, 14.30%) in 2020-2021, and employee salary costs and operating costs in 2022 (14.19%, 4.35%). However, revenue and profit outputs need to be improved (27.94%, 32.45%) in 2020, (26.27%, 30.70%) in 2021, and (25.71%, 30.45%) in 2022. DMU 2 does not require efficiency improvement as it reached 100% from 2017 to 2022.